Perancangan Proses Penyimpanan Limbah Bahan Berbahaya dan Beracun di PT. E-T-A Indoneisa - Megawati, Megawati Megawati; Panjaitan, Togar WS (Jurnal Titra, 2015)
PT. E-T-A Indonesia is a company which involves in circuit breaker industry. The process of production results in waste which categorized as dangerous and toxic waste (B3) and only saved by the company in few months. Currently, the company only own Temporary storage facilities for B3 waste which is not in accordance with Government policy which stated in PP. Thus there is a need for the company to plan the development of B3 waste storage facilities. The development of B3 waste storage facilities starts with planning the process of storing B3 waste, the process in handling contingency situation, and the designing process to develop the temporary storage facilities for B3 waste. Document which added is logbook and checklist to help the process of storing B3 waste. The results of this improvement will allows PT. E-T-A Indonesia to get the permission to store B3 waste from the government. Other positive effect by applying this improvement is to improve the safety and health condition of employees working around B3 waste storage facilities.